The dead zone [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2017)
Johnny Smith awakens from a five-year coma after his car accident and discovers that he can see people's futures and pasts when he touches them. Many consider his talent a gift; Johnny feels cursed. His fiance married another man during his coma and people clamor for him to solve their problems. When Johnny has a disturbing vision after he shakes the hand of an ambitious and amoral politician, he must decide if he should take drastic action to change the future.